Illness and Injuries in Elite Football Players—A Prospective Cohort Study During the FIFA Confederations Cup 2009 - Theron, N.; Schwellnus, M.; Derman, W.; Dvorak, J. (Clinical Journal of Sport Medicine, 2013)
Objective: The incidence of injury during elite-level football tournaments has been well documented, but the incidence of illness and medical conditions has not been well studied. The main objective was to analyze the incidence and nature of medical illnesses and injuries in football players.